2016
DOI: 10.17656/jzs.10632
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Uniaxial Compressive Strength and Modulus of Elasticity with Point Load Strength Index, Pulse Velocity and Dry Density of Limestone and Sandstone Rocks in Sulaimani Governorate, Kurdistan Region, Iraq.

Abstract: The Uniaxial Compressive Strength (UCS) of rocks is important parameter in design of geotechnical engineering. If the rocks are affected by weathering agents, there will be difficult to obtain intact samples and to determine UCS in laboratory.Hence, the use of another engineering index of rocks as an alternative for determining UCShave been studied and investigated by researchers. The Pulse Velocity and Point Load tests are used as a quick, easy and non-expensive means of obtaining rock strength indexes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…For dry and saturated siltstones: where Est and Is(50) are expressed in GPa and MPa, respectively. Similar findings were reported by Daoud et al (2017) and can be inferred from Kurtulus et al (2012) (Fig. 10).…”
Section: Is(50) and Est Correlationssupporting
confidence: 90%
“…For dry and saturated siltstones: where Est and Is(50) are expressed in GPa and MPa, respectively. Similar findings were reported by Daoud et al (2017) and can be inferred from Kurtulus et al (2012) (Fig. 10).…”
Section: Is(50) and Est Correlationssupporting
confidence: 90%
“…With respect to the ratios between E st and I s(50) (k EI =E st /I s(50) ) and between E st and BTS (k EB =E st /BTS) the obtained values were k EI =6.72 and k EB =4.51, respectively. These numbers were smaller than those proposed by Daoud et al (2017) for limestones and sandstones (k EI =11.4) but greater than those found by Raj and Pedram (2015) for rhyolites and basalts (k EB =2.1).…”
Section: Relationships Between Mechanical Parameters Of Calcarenitescontrasting
confidence: 68%
“…Fig. 11.b shows the proposed correlations as well as a power function proposed by Daoud et al [21] for Iraqi limestones and sandstones, as well as a lineal correlation inferred from the data obtained by Kurtulus et al [32] for Turkish serpentinized rocks. These derived correlation functions are very practical to obtain indirectly the strength and the deformability of soft calcarenites (like yellow varieties), in which to extract intact core samples to carry out UCS and Est test is quite difficult.…”
Section: Correlations Between Mechanical Properties In Dry and Saturamentioning
confidence: 73%
“…Similarly, few studies have proposed correlations between Is(50) and Est. Specifically, Dauod et al [21] found a power correlation function between both parameters for Iraqi sedimentary rocks. In this line, it is important to note that Point Load Test (PLT) is an alternative indirect method to obtain UCS and Est which has some strong points as its simplicity, flexibility in terms of the specimen's shape and size, low cost and the possibility of being performed in the laboratory or in the field.…”
Section: Introductionmentioning
confidence: 99%